Joseph Conable Thomas papers - Thomas, Joseph Conable, 1833-1906.
Correspondence, orders, military documents, list of chaplains, accounts, receipts, and other papers relating chiefly to Thomas's cooperation with the United States Christian Commission and the United States Sanitary Commission in their establishment of libraries for the U.S. Army of the Cumberland in Tennessee during and following the Civil War.
Clergyman and military chaplain assigned to 88th Illinois Infantry Regiment.
Collection material in English.
Keywords: United States. -- Army -- Chaplains; United States. -- Army. -- Illinois Infantry Regiment, 88th (1862-1865); United States. -- Army of the Cumberland; United States Christian Commission; United States Sanitary Commission; Reconstruction (U.S. history, 1865-1877) -- Tennessee; Soldiers' libraries -- Tennessee; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Civilian relief; United States -- History -- Civil War, 1861-1865 -- War work; Chaplains, Military; Clergy